Personal, behavioural and socio-environmental correlates of emerging adults' sustainable food consumption in a cross-sectional analysis - Elizabeth Ludwig-Borycz; Dianne Neumark-Sztainer; Nicole Larson; Ana Baylin; Andrew D Jones; Allison Webster; Katherine W Bauer (Cambridge University Press, 2023)
Abstract Objective: Describe how dietary intake patterns of US young adults align with the EAT-Lancet Planetary Health Diet (PHD) sustainable diet goals and identify personal, behavioural, and socio-environmental correlates of sustainable intake. Design: Data on past-year dietary intake were captured using a FFQ. The PHD was applied to specific food groups, and a total PHD score was calculated. Linear regression models were used to identify associations between personal, behavioural and socio-environmental factors and PHD scores. Setting: This cross-sectional analysis uses data from the second wave of EAT 2010-2018 (Eating and Activity over Time), a population-based longitudinal study recruited in Minnesota. Participants: Ethnically/racially diverse group of participants (n 1308) with a mean age of 22·1 (sd 2·0) years. Results: The mean PHD score was 4·1 (sd 1·4) on a scale of 0-14, with 14 representing the most sustainable. On average, participants consumed fewer whole grains, fish, legumes, soya, and nuts than ideal for a sustainable diet, and an excess of eggs, added sugar, and meat. The PHD score was higher for participants with higher socio-economic status (SES) and greater educational attainment. Higher home availability of healthy food (β = 0·24, P < 0·001) and less frequent fast-food consumption (β = -0·26, P < 0·001) were the strongest correlates of PHD scores. Conclusions: Results suggest that a high percentage of participants may not be achieving the sustainable diet goals defined by the PHD. Reductions in meat consumption and increases in plant-based foods are necessary to increase the sustainability of US young adults' diets.